Digital Transformation of Commercial Banks in the Practice of Uzbekistan (Eurasian Scientific Herald, 2023)
Digital transformation is now seen as a new paradigm. Changes in the nature of banks during the implementation of their transformations can become an impetus for development for entire industries. Digital modernization gives traditional banks a new chance to improve customer satisfaction and loyalty, fostering long-term relationships. This article is devoted to the study of current trends, problems, and prospects for the digital transformation of the Uzbek banking sector. The main performance indicators of second-tier banks of the Republic of Uzbekistan are analyzed, an overview is given of the specifics of the functioning of the banking sector in the digital economy and the main problems that arise during their activities.